Protein and Amino Acid Profile of Filial Etawah Crossbred and Castrated Filial Boer Crossbred Goat Meat - Hari Purnomo; Djalal Rosyidi; Sayoga Kristian Pantoro (Faculty of Animal Science Universitas Brawijaya, 2012)
The aim of this study was to know the protein content and amino acid profile of filial Etawah and castrated Boer goat meat. The results were expected to be used as information about protein content and amino acid composition of filial Etawah and filial castrated Boer goat meat and as a reference for further experiment about different livestock. The material of the research were loin meat, front and back thigh of filial Etawah and filial castrated Boer goat meat. Data were analysed with t-test. The results showed that castrated filial Boer goat meat had significantly higher protein content and 7 essensial amino acids namely lysine, leucine, arginine, phenylalanine, isoleucine, valine and histidine compared to the one from filial Etawah goat meat. Key words: protein, amino acid profiles, goat meat